Out Patient Laparoscopy Analgesic Efficacy of Buprenorphine - Aurangzeb, Muhammad; Ahmad, Shafiq (Journal of Postgraduate Medical Institute, 2011)
100 cases were randomly allocated to two groups A & B , 50 cases in each group. Group A received 2 ug/kg of buprenorphine. (Temgesic) I/V. While group B received 10 mg valium + 5 mg Haloparidol (Serenaace) I/V. Both groups were given peri-umbilical block with 10 ml of 2% Xylocaine. Analgesic efficacy and recovery profile of group A was compared with that of group B. Group A showed statistically better results in terms of both intra-operative analgesia and degree to reflex rigidity of abdominal muscles as well as in post-operative grading to pain and recovery profile. None of the patients showed any sign or symptom suggestive of respiratory embarrassment.